2002
DOI: 10.1039/b201180h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pd-mordenite pretreatment on the heterogeneity of Heck catalysisElectronic supplementary information (ESI) available: XRD patterns, TEM and SEM images. See http://www.rsc.org/suppdata/cc/b2/b201180h/

Abstract: In Heck reactions with tributylamine as the base and in toluene, Pd(NH3)4(2+)-mordenite (0.4 wt% Pd) and Pd0-mordenite (0.4 and 4 wt% Pd) are not only active and selective, but also truly heterogeneous catalysts, while oxidized PdII species in an all-oxygen environment, i.e. ionic Pd2+ or PdO, are prone to leaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…However, it has been shown that the catalytic activity of supported palladium catalysts is significantly lower than that achieved with palladium phosphine ligands [19,20]. For instance, palladium-exchanged zeolites and Pd/Cu hydrotalcites are active catalysts for the Suzuki, Heck, Sonogashira, and cycloisomerization reactions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 96%
“…However, it has been shown that the catalytic activity of supported palladium catalysts is significantly lower than that achieved with palladium phosphine ligands [19,20]. For instance, palladium-exchanged zeolites and Pd/Cu hydrotalcites are active catalysts for the Suzuki, Heck, Sonogashira, and cycloisomerization reactions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 96%
“…These Pd-species could be retained in the zeolite pores or re-adsorbed at the surface through a dissolution-readsorption equilibrium. Recently, Dams et al [51,52] revisited the Heck reaction catalyzed by Pd-zeolite and proposed that the activity of these heterogeneous catalysts depends on the thermal treatment. The Pd(II)-species surrounded by oxygen inside the zeolites pores are prone to leaching, the leached Pd-species reflecting the overall activity of the catalyst through a homogeneous cycle whereas the [Pd(NH 3 ) 4 ] 2+ -species or the Pd(0)-particles entrapped in the zeolite pores would remain true heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%
“…[110][111][112][113] Although many efforts to prepare solid-phase catalysts for the Heck reaction have been made, homogeneous catalytic systems have advantages on catalytic activity. [114][115][116][117][118][119][120][121][122] In fact, it was known that designing recyclable system for the Heck reaction was more challenging than that for the Suzuki-Miyaura reaction. These catalysts were less stable under the Heck reaction condition, and thus often decompose physically or chemically.…”
Section: Development Of a Novelmentioning
confidence: 99%